PENGARUH PENERAPAN METODE DISKUSI TIPE BUZZ GROUP TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII.4 DAN VIII.6 SMPN 14 PADANG TAHUN PELAJARAN 2013/2014 - Fujianti, Hikmah; Zulfaneti, Zulfaneti; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
This research based on the students understanding of mathematical concepts are still low. This study aims to determine whether students understanding of mathematical concepts by applying Discussion Method Type Buzz Group better than students understanding of mathematical concepts with the application of conventional learning. This type of research is experimental, the research design static group comparison. The population in this research is the students in grade VIII SMPN 14 Padang. Sampling was done by purposive sampling, with the consideration that both classes have an average that is similar to the decision classes VIII.6 and VIII.4 as samples. The instrument in this research is essay test with reliabilitas = 0,85. Results of data analysis that the two classes are normally distributed and homogeneous samples at the level of Î± = 0,05 and t test results obtained P-value = 0,000 is less than Î± = 0,05. It can be concluded that the students understanding of mathematical concepts by applying Discussion Method Type Buzz Group VIII.4 grade better than students understanding of mathematical concepts by applying conventional learning models VIII.6 grade SMP 14 Padang with 95% confidence level.